Pura Desa Batuan sebagai Media Pendidikan Multikultural Melalui Pariwisata - Ni Wayan Karmini (UHN IGB Sugriwa Denpasar, 2017)
ali tourism dynamics are reflected by the use of the village temple as a tourist attraction.This paper discusses the Impact of Development of Tourism activity in Pura Desa Batuan to thesocio-economic life of the local community, and cultural tourism object “pura desa batuan” asmedia of multicultural education. This paper is the result of qualitative research. The process ofdata collection is done by observation, literature study and in-depth interviews with 10informants manager Pura Desa Batuan and tourists who visit the attraction Pura Desa Batuan.Data analysis was performed by descriptive, qualitative and interpretative by applying the theoryof commodification of tourism development. The results showed that Pura Desa Batuan hasbecome a tourist attraction in Bali that selected by travelers, the travel commodity to benefitlocal communities. The presence of tourists has raised entrepreneurship and supportingdevelopment manners Batuan Village People. In addition, a cultural attraction Pura Desa Batuanis also as a medium of multicultural education. Tourist activity in Pura Desa Batuan village thatis capable of generating economic activity and strengthen the cultural traditions of localcommunities and raise awareness of this multicultural needs to be maintained and developed